Taxonomic diversity of broad-leaf weeds at Bangladesh Agricultural University campus and their ethno-botanical uses: Broadleaved weeds diversity and their ethno-botanical uses (Journal of the Bangladesh Agricultural University, 2019)
An intensive survey and literature review was furnished to study taxonomic diversity and ethno-botanical uses of broad-leaf weeds available in BAU campus. Availability of 107 broad-leaf weed species has been identified and those belong to 78 genera and 38 families. Among the families, Fabaceae is best-represented with 13 weed species followed by Euphorbiaceae and Amaranthaceae (seven species in each), Solanaceae (six species), Convolvulaceae and Polygonaceae (five species); 17 families are represented by two to four species while 15 families by single species in each. The genera viz. Desmodium, Ludwigia and Solanum, are represented by four species in each followed by Amaranthus, Ipomoea, Lindernia, Persicaria and Senna three species in each; however, most of the genera are represented by one or two species in each. Three distinct phenology (flowering periods) viz. October-March (52), April-September (40) and all the year-round (15), were observed among identified weed species and the knowledge on phonological development would be helpful to know soil seedbank potential for their effective management. These weed species possess many ethno-botanical uses e.g., medicinal value, consumed as vegetable, feed, fodder, etc. This study provides information on ethno-botanic uses, taxonomic diversities and phenology of the broad-leaf weeds for their effective management.J Bangladesh Agril Univ 17(4): 526–538, 2019